A preparation method for the highly permeable ceramic microfiltration membrane – precursor film firing method. Issue 6 (12th January 2018) - Yin, Xiaoqin; Guan, Kang; Gao, Peng; Peng, Cheng; Wu, Jianqing
Abstract : A new technique is proposed to improve the permeance of ceramic membranes. Abstract : A method called the precursor film firing method is proposed to improve the permeance of ceramic microfiltration membranes by avoiding intermediate layer and dip-coating process, and efficiently control the thickness of the separation layer. In this method a precursor film is prepared independently of the support by a film coating machine. This precursor film consists of two layers: Al2 O3 /PVA layer made of Al2 O3 powder and polyvinyl alcohol (PVA), and polyvinyl butyral (PVB) layer. The precursor film is pasted on the support and fired to obtain membranes. Because the intermediate layer and dip-coating process are avoided in this method, the fabricated membranes show high permeance. For the fabricated membrane with average pore size = 0.18 μm and separation layer thickness = 10.7 μm, the permeance is 3890 L m −2 h −1 bar −1 . Also the separation layer thickness can be controlled efficiently. And the precursor film can be used on fabricate curved membranes such as cylindrical membranes.